Responder
1. ∫ x³⁄(x – 5) dx = (x³)/3 + (5x²)/2 + 25x + 125 ln|x – 5| + C
2. ∫ (7x – 7)/(x² – 5x – 6) dx = 5 ln|x – 6| + 2 ln|x + 1| + C
3. ∫ 3⁄[(x + 1)(x² – x)] dx = –3 ln|x| + (3⁄2) ln|x – 1| + (3⁄2) ln|x + 1| + C
Solución
We will evaluate the following integrals using the method of partial fractions:
1) ∫ x³⁄(x – 5) dx
2) ∫ (7x – 7)/(x² – 5x – 6) dx
3) ∫ 3⁄[(x + 1)(x² – x)] dx
Below are the step‐by‐step solutions.
────────────────────────────
1) ∫ x³⁄(x – 5) dx
Step 1. Since the degree of the numerator (3) is greater than that of the denominator (1), we start with polynomial division.
Divide x³ by (x – 5):
• Divide: x³ ÷ x = x²
Multiply back: x² · (x – 5) = x³ – 5x²
• Subtract:
x³ – (x³ – 5x²) = 5x²
• Bring down the “0x” (if you wish to keep the process formal) and continue:
Divide: 5x² ÷ x = 5x
Multiply back: 5x · (x – 5) = 5x² – 25x
• Subtract:
5x² – (5x² – 25x) = 25x
• Next, divide: 25x ÷ x = 25
Multiply back: 25 · (x – 5) = 25x – 125
• Subtract:
25x – (25x – 125) = 125
Thus, we have:
x³⁄(x – 5) = x² + 5x + 25 + 125⁄(x – 5).
Step 2. Now integrate term‐by‐term:
∫ x³⁄(x – 5) dx = ∫ (x² + 5x + 25) dx + 125 ∫ 1⁄(x – 5) dx
Compute the integrals:
∫ x² dx = (x³)/3
∫ 5x dx = (5x²)/2
∫ 25 dx = 25x
∫ 1⁄(x – 5) dx = ln|x – 5|
Thus the answer is:
(x³)/3 + (5x²)/2 + 25x + 125 ln|x – 5| + C
────────────────────────────
2) ∫ (7x – 7)/(x² – 5x – 6) dx
Step 1. Factor the denominator. Notice:
x² – 5x – 6 = (x – 6)(x + 1).
Step 2. Write the integrand in partial fractions:
(7x – 7)/[(x – 6)(x + 1)] = A⁄(x – 6) + B⁄(x + 1).
Multiply both sides by (x – 6)(x + 1):
7x – 7 = A(x + 1) + B(x – 6).
Step 3. Solve for A and B. Expand the right-hand side:
A(x + 1) + B(x – 6) = (A + B)x + (A – 6B).
Equate coefficients with 7x – 7:
Coefficient of x: A + B = 7
Constant term: A – 6B = –7
Solve:
From A + B = 7, we get A = 7 – B.
Substitute into A – 6B = –7:
(7 – B) – 6B = –7 ⟹ 7 – 7B = –7 ⟹ –7B = –14 ⟹ B = 2.
Then A = 7 – 2 = 5.
Step 4. Write and integrate:
∫ (7x – 7)/(x² – 5x – 6) dx = 5 ∫ 1⁄(x – 6) dx + 2 ∫ 1⁄(x + 1) dx
= 5 ln|x – 6| + 2 ln|x + 1| + C
────────────────────────────
3) ∫ 3⁄[(x + 1)(x² – x)] dx
Step 1. Factor the quadratic part:
x² – x = x(x – 1).
Thus, the denominator becomes:
(x + 1)x(x – 1).
Step 2. Write the partial fractions decomposition:
3⁄[x(x – 1)(x + 1)] = A⁄x + B⁄(x – 1) + C⁄(x + 1).
Multiply through by x(x – 1)(x + 1):
3 = A (x – 1)(x + 1) + B x(x + 1) + C x(x – 1).
Simplify each term:
A (x – 1)(x + 1) = A (x² – 1)
B x(x + 1) = B (x² + x)
C x(x – 1) = C (x² – x).
Combine like terms:
3 = (A + B + C)x² + (B – C)x – A.
Step 3. Equate coefficients with the constant 3 (which is 0·x² + 0·x + 3):
Coefficient of x²: A + B + C = 0
Coefficient of x: B – C = 0
Constant term: –A = 3 ⟹ A = –3
From B – C = 0, we have B = C. Then from A + B + C = 0:
–3 + 2B = 0 ⟹ 2B = 3 ⟹ B = 3⁄2, and C = 3⁄2.
Step 4. Write the decomposition and integrate:
3⁄[x(x – 1)(x + 1)] = –3⁄x + (3⁄2)⁄(x – 1) + (3⁄2)⁄(x + 1).
Thus, the integral becomes:
∫ 3⁄[(x + 1)(x² – x)] dx = –3 ∫ 1⁄x dx + (3⁄2) ∫ 1⁄(x – 1) dx + (3⁄2) ∫ 1⁄(x + 1) dx
= –3 ln|x| + (3⁄2) ln|x – 1| + (3⁄2) ln|x + 1| + C
────────────────────────────
Final Answers:
1) ∫ x³⁄(x – 5) dx = (x³)/3 + (5x²)/2 + 25x + 125 ln|x – 5| + C
2) ∫ (7x – 7)/(x² – 5x – 6) dx = 5 ln|x – 6| + 2 ln|x + 1| + C
3) ∫ 3⁄[(x + 1)(x² – x)] dx = –3 ln|x| + (3⁄2) ln|x – 1| + (3⁄2) ln|x + 1| + C
These are the integrals evaluated using the method of partial fractions.
Revisado y aprobado por el equipo de tutoría de UpStudy
![](/pmw/light_bulb.png?etag=525fd69ac661e11754e2fc9f1b18a4ee)
Explicar
![](/pmw/spiral_notepad.png?etag=abe3906b7558c543a7b30ba53a3b5a5b)
Simplifique esta solución